(3OjhGf GdeJfHis - (3CMeO Hf GdMSjf Hf GdMSf Hf YHO GdUeO Hf GdLYaj Gdchaj GdeJfHj, CHh GdWjH, J (B354 (3g` s; (3CHhGdWjH CMeO Hf GdMSjf Hf GdMSf Hf YHO GdUeO Hf GdLYaj Gdchaj GdeYQha H` CHj GdWjH GdoeJfHj,J (B354 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi eGaJM ef GdYhGQa hCdge ef GdeYGQa hChd TYQ GdOjhGf (B: (3Cef GROjGQc ai GdOLi GdQbjGA EP MjK cfJ ef GdXdGe VjGA s
(3BNQgG (B:s
(3hef LgdJ faSg bOQg QCi ZjQg efg eGdGjQi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHI s
(3eQJH Ydi MQha GdeYLe GdeZQHi hHChdg ebOeI dCHj LeYI GdeQGcTi GdeYQha HGdeZhS s
(3UOQJ GdbUGFO HGdefGSHGJ GdJi bjdJ ajgG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B115 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B201s
Keywords: (3GdCOHs